Numéro 1 Beaux- Arts Grenoble. (Grenoble : Ecole des Beaux-Arts de Grenoble, 1989)
Baccouche, Houssem ; Buenerd, Renaud ; Donadel, Daniel ; Duverney-Guichard, Thierry ; Melchiors, Christine ; Monnier, Richard ; Sadrin, Laurent ; Sarrazin, Pascal ; Simon, Klaus
boek